Tumor microenvironment penetrating chitosan nanoparticles for elimination of cancer relapse and minimal residual disease - Mahmudi, Hossein; Adili-Aghdam, Mohammad Amin; Shahpouri, Mohammad; Jaymand, Mehdi; Amoozgar, Zohreh; Jahanban-Esfahlan, Rana (Frontiers in Oncology, 2022)
Chitosan and its derivatives are among biomaterials with numerous medical applications, especially in cancer. Chitosan is amenable to forming innumerable shapes such as micelles, niosome, hydrogel, nanoparticles, and scaffolds, among others. Chitosan derivatives can also bring unprecedented potential to cross numerous biological barriers. Combined with other biomaterials, hybrid, and multitasking chitosan-based systems can be realized for many applications. These include controlled drug release, targeted drug delivery, post-surgery implants (immunovaccines), theranostics, biosensing of tumor-derived circulating materials, multimodal systems, and combination therapy platforms with the potential to eliminate bulk tumors as well as lingering tumor cells to treat minimal residual disease (MRD) and recurrent cancer. We first introduce different formats, derivatives, and properties of chitosan. Next, given the barriers to therapeutic efficacy in solid tumors, we review advanced formulations of chitosan modules as efficient drug delivery systems to overcome tumor heterogeneity, multi-drug resistance, minimal residual disease, and metastasis. Finally, we discuss chitosan NPs for clinical translation and treatment of recurrent cancer and their future perspective.